Evaluasi Kinerja Internal Sebagai Bagian dari Manajemen Strategik - Mohamad Afrizal Miradji; Putri Ayu Aisyah; Chika Aulia Putri; Fadensyah Muhammad Daffa Effendi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Internal performance evaluation is an essential process within strategic management, aimed at assessing a company's internal capabilities to achieve its strategic goals. This evaluation involves a comprehensive analysis of key internal components, including human resources, finance, operations, and marketing. The primary objective is to identify internal strengths and weaknesses, along with external opportunities and threats that may influence organizational performance. This study employs a qualitative research method to explore how internal evaluations contribute to strategic decision-making. The findings suggest that regular and systematic internal performance evaluations can serve as a strong foundation for formulating effective strategies, improving operational efficiency, and enhancing competitive advantage in the market. Thus, internal performance evaluation plays a vital role in supporting the strategic development and long-term sustainability of a company.